RETRACTED: On the issue of building an integrated waste management system: World practice and its application in the Russian Federation - Zavolokina Liudmila; Diesperova Natalia (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001